Environmental Policies: An analysis for 51 countries between the years 1991 to 2012 - Maciell, Harine Matos; Maciell, Wlisses Matos [UNESP] (My University, 2018)
The objective of this article was to analyze the environmental policies adopted by 51 countries through their results regarding the forest area, total emissions of greenhouse gases and the consumption of renewable energies. All countries have reduced their consumption of renewable energy. Average forest areas have also declined. The countries with the largest forest areas are Russia, Brazil, Canada and the United States. The countries that most polluted were the United States and China.

O objetivo deste artigo foi analisar as políticas ambientais adotadas por 51 países através dos seus resultados referentes a área de florestas, emissões totais dos gases do efeito estufa e o consumo de energias renováveis. Todos os países diminuíram seus consumos de energias renováveis. A média das áreas de florestas também diminuiram. Os países com maiores áreas de florestas são Rússia, Brasil, Canadá e Estados Unidos. Os países que mais poluiram foram os Estados Unidos e China.
Políticas Ambientais: Uma análise para 51 países entre os anos de 1991 a 2012
Keywords: Energia Renovável; Floresta; Forest; Natural Resources; Recursos Naturais; Renewable Energy